Epicardial prestrained confinement and residual stresses: a newly observed heart ventricle confinement interface. Issue 152 (29th March 2019) - Shi, Xiaodan; Liu, Yue; Copeland, Katherine M.; McMahan, Sara R.; Zhang, Song; Butler, J. Ryan; Hong, Yi; Cho, Michael; Bajona, Pietro; Gao, Huajian; Liao, Jun
Abstract : The heart epicardial layer, with elastin as the dominant component, has not been well investigated, specifically on how it contributes to ventricular biomechanics. In this study, we revealed and quantitatively assessed the overall status of prestraining and residual stresses exerted by the epicardial layer on the heart left ventricle (LV). During porcine heart wall dissection, we discovered that bi-layered LV surface strips, consisting of an epicardial layer and cardiac muscle, always curled towards the epicardial side due to epicardial residual stresses. We hence developed a curling angle characterization technique to intuitively and qualitatively reveal the location-dependency and direction-dependency of epicardial residual stresses. Moreover, by combining prestrain measurement and biaxial mechanical testing, we were able to quantify the epicardial prestrains and residual stresses on the unpressurized intact LV. To investigate the potential mechanical effect of epicardial prestraining, a finite-element (FE) model has been constructed, and we demonstrate that it is the prestraining of the epicardial layer, not the epicardial layer alone, providing an additional resistance mechanism during LV diastolic expansion and ventricular wall protection by reducing myocardial stress. In short, our study on healthy, native porcine hearts has revealed an important phenomenon—the epicardial layer, rich in elastin, acts like a prestrained 'balloon' that wraps around the heart and functions as an extra confinement and protection interface. The obtained knowledge fills a gap in ventricular biomechanics and will help design novel biomimicking materials or prosthetic devices to target the maintenance/recreation of this ventricle confinement interface.